New excavation of the Roman Age settlement at Budapest dist. XVII, Péceli út (15127) site - Simon, Bence; Benes, Anita; Joháczi, Szilvia; Barna, Ferenc (Dissertationes Archaeologicae, 2020)
In autumn 2019 the staff of the Institute of Archaeological Sciences conducted a rescue excavation in the suburbs of Budapest, on the territory of Pécel. Based on the long research history of the investigated site (Budapest dist. XVII, Péceli út) a settlement of the Imperial Period was expected. The excavation confirmed the expectations and two buildings, several ditches, an outdoor oven and numerous refuse pits were unearthed from the 3rd–4th century AD. The features contained many Samian ware fragments, which shed light on the Roman-Barbarian trade relations during the middle Imperial Period.